Developing English Reading Material for The Tenth Grade of Computer and Network Engineering Students at SMK N 4 Payakumbuh - Wahyuningsih Wahyuningsih; Veni Roza; Eliza Eliza; Genta Sakti (Jurnal Pendidikan dan Sastra Inggris, 2023)
There are several problems found in this research, such the material used by teacher was not related to the major, textbook for students was not provide the material related to their major, and the material only taken from the internet by teacher randomly. This research is research and development which uses the theory of Sugiyono. The stages in this development are research, developing, validation, and testing. The subjects in this study were 36 students from the tenth grade of Computer and Network Engineering. The need analysis shows, students want to learn reading material that is related to their major and useful when they work after graduation. For validation by expert, the English reading material is categorized as "Very Valid" with the percentage score obtained is 83%. The practical results that have been given to teacher and students, the English reading material is categorized as "Very Practice" with score 92%. And the last, the effectiveness of the English reading material is effective, it gets a significant value of 0.00 which is <0.05,it means that the English reading material is effective. So overall, the developing of English reading material is accordance with the needs of students majoring in computer and network engineering.